KERJA SAMA ANTAR GURU DI SMP ISLAM TERPADU BABUSSALAM KUALA KAPUAS - Nurul Fitriah (JURNAL SOCIUS, 2013)
Ideally the relationship among teachers in a school is harmonious so that the teaching and learning process in the school can be well established. The purpose of this research was to determine the of cooperation among teachers, teachers perceptions on cooperative relationships in schools and the factors that affect the cooperative relationships among teachers in junior high school IT Babussalam Kuala Kapuas.This study used qualitative methods that took place in junior high school IT Babussalam Kuala Kapuas. The data sources consisted of 16 teachers, the selection of data sources were based on a purposive sampling technique. The results of this research showed that (1) in general the cooperation among PNS/GTD, GTY and GTT teachers at junior high school IT Babussalam Kuala Kapuas is adequately good, it could be seen through the teaching and learning process  which has worked well all day and the other planned activities which have been  implemented; (2) regarding the teachers perceptions on cooperation among teachers in junior high school IT  Babussalam Kuala Kapuas, there are 12 teachers who have adequately good perception, two teachers who still have less perception, and two other teachers who have good perception; (3) the factors that affected the cooperation among GTD/PNS, GTY and GTT teachers at  junior high school IT Babussalam Kuala Kapuas were  communication, the existence of clear objectives, a sense of responsibility, mutual understanding, sincerity in work and mutual aids in performing the task, as well as  trust among teachers. Key words: Teachers cooperation